2014
DOI: 10.22226/2410-3535-2014-4-279-282
|View full text |Cite
|
Sign up to set email alerts
|

On the structural changes in the nickel-base alloy EI893 during operation

Abstract: Institute of problems of mechanical engineering, RAS, 85 Belinsky st., 03024, Nizhny Novgorod, Russia A comparative qualitative and quantitative analysis of the microstructure and phase composition of the alloy EI893 (KhN65VMTYu) was performed, on the example of turbine rotor blades with different operating times. The characteristic changes in the parameters of strengthening phases were revealed, which allows to judge about the degree of degradation of the material structure during operation and the possibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The changes in the microstructure of nickel-based alloys, in particular, the material HN65VMTU, after workings for 53000 -112000 hours, are considered in and it is shown that the structural-phase state changes significantly, degrades [20,21]. After heat treatment (annealing), the hardening intermetallic γ'-phase (Ni3Al, Ti) practically completely dissolved in the solid solution, and its residues have a chaotic distribution over the grain volume.…”
Section: The Influence Of Hardening Methods On the Quality Of The Sur...mentioning
confidence: 99%
“…The changes in the microstructure of nickel-based alloys, in particular, the material HN65VMTU, after workings for 53000 -112000 hours, are considered in and it is shown that the structural-phase state changes significantly, degrades [20,21]. After heat treatment (annealing), the hardening intermetallic γ'-phase (Ni3Al, Ti) practically completely dissolved in the solid solution, and its residues have a chaotic distribution over the grain volume.…”
Section: The Influence Of Hardening Methods On the Quality Of The Sur...mentioning
confidence: 99%